(untitled) (Estudios de Historia de España, 2022)
The Great Depression of the 1930s brought back to Spain thousands of emigrants who had settled in different regions of Latin America. The governments of the Second Republic were faced for the first time with the need to legislate not so much on outward emigration as on mass returns. The problem of reducing mass emigration was discussed in the Cortes sessions and gave rise to a parallel public debate in the press, especially with regard to state intervention in the repatriation of Spaniards affected by the crisis and the management and financing of the passages of those whose situation was unsustainable. However, beyond the specific discussion of this contingency, the interventions of the deputies responded to the different opinions that were circulating at the time about the economic role of emigrants and the consequences that their return would have for the country. This study analyses the view of the decline of the Spanish migratory phenomenon through the republican legislature and the regional and national press.